A-021 Normative Data on Montreal Cognitive Assessment Total Scores in Healthy Controls. (28th August 2020) - L, Ratcliffe; C, Marker
Abstract: The Montreal Cognitive Assessment (MoCA) is considered to be a suitable, sensitive, and specific cognitive screening tool for detecting mild cognitive impairment. Research has reported variable cutoff scores for the MoCA based upon geographical location. The aim of the present study is to provide normative data in a sample of cognitively healthy adults. Data was collected through the National Alzheimer's Coordinating Center (NACC). A population of healthy adults (N = 3610) was examined (66% female, 78% Caucasian, 16% African American, 6% Other). MoCA normative data were derived from age and education, which were found to be weakly but significantly associated with age (r = −.203, p = .000) and more strongly correlated with education (r = .402, p = .000). Total scores (M = 26.25, SD = 2.75) were at the suggested cutoff for impairment (< 26). Based on an ANOVA, age had a significant effect on MoCA scores (F (6, 3603) = 25.30, p < .001). A second ANOVA revealed that education also had a significant effect on MoCA scores (F (2, 3582) = 290.56, p < .001). Individuals with higher levels of education obtained higher MoCA scores. Performance was also found to decrease slightly with age. Therefore, clinicians should use caution when applying the recommended cutoff scores.